2016
DOI: 10.1186/s12913-016-1843-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient activation in older people with long-term conditions and multimorbidity: correlates and change in a cohort study in the United Kingdom

Abstract: BackgroundPatient Activation is defined as the knowledge, skill, and confidence a patient has in managing their health. Higher levels of patient activation are associated with better self-management, better health outcomes, and lower healthcare costs. Understanding the drivers of patient activation can allow better tailoring of patient support and interventions. There are few data on patient activation in UK patients with long-term conditions.MethodsA prospective cohort design was used. Questionnaires were mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
81
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 44 publications
(58 reference statements)
20
81
0
1
Order By: Relevance
“…In the multivariable regression analyses, increase in age, PHI, and baseline PAM scores were signi cant predictors of PAM scores at the 12-month follow-up. Increase in years of age as a signi cant determinant of reduced activation is consistent with ndings of studies by Blakemore et al and Overbeek et al [38,39]. Preliminary qualitative feedback of the WellNet program showed that some elderly patients reported di culty in engaging with the online GoShare tool and MediTracker mobile application, thereby needing more assistance and coaching to access the electronic educational programs.…”
Section: Discussionsupporting
confidence: 85%
“…In the multivariable regression analyses, increase in age, PHI, and baseline PAM scores were signi cant predictors of PAM scores at the 12-month follow-up. Increase in years of age as a signi cant determinant of reduced activation is consistent with ndings of studies by Blakemore et al and Overbeek et al [38,39]. Preliminary qualitative feedback of the WellNet program showed that some elderly patients reported di culty in engaging with the online GoShare tool and MediTracker mobile application, thereby needing more assistance and coaching to access the electronic educational programs.…”
Section: Discussionsupporting
confidence: 85%
“…Overbeek et al [39,40]. It is reported that older adults have limited self-management skills as a result of having greater number of chronic conditions which are often associated with poor quality of life, reduced functional status and increased disabilities [39,41]. Consistent with the above study findings, WellNet group observed a higher mean number of co-existing chronic conditions among patients who were over the median age of 70 years compared to those who were less than or equal to 70 years.…”
Section: Baseline Vs Follow-up Pam Levelsmentioning
confidence: 56%
“…Overbeek et al [39,40]. It is reported that older adults have limited self-management skills as a result of having greater number of chronic conditions which are often associated with poor quality of life, reduced functional status and increased disabilities [39,41].…”
Section: Baseline Vs Follow-up Pam Levelsmentioning
confidence: 99%
“…Persistent actuation was low in those sort 2 diabetes patients with comorbidities. Essentially, in past examinations number of comorbidities and number of confusions were adversely connected with patient enactment level [32]. This could be because of patients with comorbid infection having less capacity to adapt to numerous conditions bringing about lower dimensions of initiation [33].…”
Section: Discussionmentioning
confidence: 99%